ANALISIS PROFESIONALISME APARATUR BIROKRASI PADA SEKRETARIAT DAERAH KABUPATEN ACEH TIMUR - Safrizal UMA (PERSPEKTIF, 2015)
Studies show concrete evidence of the phenomenon, where the study took place at the Department of Population and Civil Registration East Aceh district. In that study found a variety of pathologies that have been ingrained in the self apparatus in organizing tasks and functions of the organization. Red tape such as pathology, extortion, waiting for instructions tops, and more. In this study also found the major factors hindering the professionalism apparatus public bureaucracy that is the existence of formal rules rigidly regulate the roles and duties of each section so that the apparatus of the Department of Population and Civil Registration East Aceh District in performing the duties and functions of the organization are not oriented to what is the organization's mission but is more likely to formal rules and instructions boss .. While the factors which will affect the professionalism of the apparatus according to this thesis is the existence of a system in which the bureaucracy operates like: vision and mission of the organization, organizational structure, leadership factor and reward systems.